1998
DOI: 10.1016/s0042-6989(97)00467-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-frequency and contrast tuning of the transient-stereopsis system

Abstract: The tuning of the transient-stereopsis system to luminance contrast and spatial-frequency (SF) was investigated with narrow-band gabor targets with a constant sigma of 1 degree. They were presented for brief (140 ms) durations and subtended a large (6 degrees) disparity. When dichoptic gabor stimuli were matched in SF (0-5 cpd), transient stereo performance was either uniform across SF or greater at frequencies below 1 cpd. When dichoptic stimuli had unmatched SF (0.5 + 0-5 cpd) and matched contrast (100%), st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…1 B, right). This result is understandable if these thresholds are measures of the observer's sensitivity either to the absolute disparity of the grating or to the relative disparity between the carrier of the grating patch and its Gaussian-windowed contrast envelope (Hess and Wilcox, 1994;Schor et al, 1998;Langley et al, 1999;McKee et al, 2004), the disparity of which was fixed at zero (or perhaps between the carrier and other, more distant reference stimuli, such as the edges of the monitor). If the observer was more sensitive to any of these disparities than to the relative disparity between the two carriers, threshold would depend little on the grating orientation difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 B, right). This result is understandable if these thresholds are measures of the observer's sensitivity either to the absolute disparity of the grating or to the relative disparity between the carrier of the grating patch and its Gaussian-windowed contrast envelope (Hess and Wilcox, 1994;Schor et al, 1998;Langley et al, 1999;McKee et al, 2004), the disparity of which was fixed at zero (or perhaps between the carrier and other, more distant reference stimuli, such as the edges of the monitor). If the observer was more sensitive to any of these disparities than to the relative disparity between the two carriers, threshold would depend little on the grating orientation difference.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps we are unable do so in the absence of intermediate orientations in the scene to serve as common reference stimuli. Alternatively, second-order stimulus features (Hess and Wilcox, 1994;Schor et al, 1998;Langley et al, 1999;McKee et al, 2004) might play this role in naturalistic scenes. Another possibility is that normalization does occur, but only among the spatially overlapping components of a single object, such as the components of the plaids used here.…”
Section: Joint Coding Of Disparity and Orientationmentioning
confidence: 99%
“…More recently, Clifton Schor and colleagues have conducted a systematic characterization of our sensitivity to depth from transient and sustained disparity (Schor et al, 2001(Schor et al, , 1998(Schor et al, , 1984Edwards et al, 2000Edwards et al, , 1999aPope et al, 1999). These studies have shown different 1) spatial tuning, 2) tendency to depth-alias, 3) orientation tuning, 4) sensitivity to spatial envelope size, and 5) tolerance for opposite polarity, for long vs. short duration depth stimuli.…”
Section: Functional Organizationmentioning
confidence: 99%
“…Several mechanisms have been suggested to reduce these false matches and compute depth correctly, such as coarse-to-fine processing (Marr and Poggio, 1979) and pooling of disparity sensor activities over positions, multiple spatial frequencies, and orientations Qian and Zhu, 1997). For textured surfaces, coarse-scale disparity information is effectively obtained using the contrast envelope Hess, 1995, 1997;Schor et al, 1998). Therefore, the notion of coarse-to-fine and multichannel pooling probably should be extended to include the additional disparity information originating from the envelopeprocessing pathway.…”
Section: Comparisons With Findings From Psychophysical and Computatiomentioning
confidence: 99%
“…Previously, a substantial number of psychophysical studies investigated binocular processing of contrast-envelope cues (Hess and Wilcox, 1994;Wilcox and Hess, 1995Schor et al, 1998;Edwards et al, 1999Edwards et al, , 2000Langley et al, 1999;McKee et al, 2004). These studies have shown that we are able to perceive depth based purely on binocular disparities of contrastenvelope cues and suggested that such stereopsis is mediated by nonlinear mechanisms that are distinct from that for extracting luminance-based cues.…”
Section: Introductionmentioning
confidence: 99%